If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -7x = 82 + -42x Solving 7 + -7x = 82 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. 7 + -7x + 42x = 82 + -42x + 42x Combine like terms: -7x + 42x = 35x 7 + 35x = 82 + -42x + 42x Combine like terms: -42x + 42x = 0 7 + 35x = 82 + 0 7 + 35x = 82 Add '-7' to each side of the equation. 7 + -7 + 35x = 82 + -7 Combine like terms: 7 + -7 = 0 0 + 35x = 82 + -7 35x = 82 + -7 Combine like terms: 82 + -7 = 75 35x = 75 Divide each side by '35'. x = 2.142857143 Simplifying x = 2.142857143
| =20+3 | | h-6j+7h+10j= | | 3.2q-3.6-4.1q=1.9q-4.8 | | 4x+27=72-2x | | 6x+39=14x-25 | | 6x^2+49-45=0 | | 3[x-5]=9 | | 25x^2=-32 | | p+10p-5-3p= | | 136-2x=34x+24 | | 6y-2(y+4)=12 | | y+11=4x | | 10+15m-6m-2m= | | 123-6x=2x+11 | | 28x-X^2=192 | | x^2*x=y | | 5-3t=6t-22 | | 52-4x=23x+16 | | 4y+4=3x | | 8p-9=-2p+7 | | 0.3(x+20)-0.05(x-10)=14 | | 6x-29=31 | | (5r-1)(6r-3)= | | 7x+9+5x=-3x+14 | | t+38=7t+8 | | 2y=x-7 | | 3x-5=11x-29 | | 8+27x+6-14x=5+10x+9+3x | | t-47=-35 | | 9p+13=3p-5 | | 3t-47=-35 | | y^2=x |